2022
DOI: 10.3390/jcm11030576
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of People with Multiple Sclerosis during the COVID-19 Pandemic

Abstract: Objective. This study assesses and compares the mental health status of people with multiple sclerosis (PwMS) in Poland during the second wave of the Coronavirus Disease 2019 (COVID-19) pandemic (November 2020) to a similar group whose mental health status was examined in November 2017. It also analyzed the psychological resources such as self-efficacy and health locus of control (HLC) and their relationship to mental health in both groups. Methods. Cross-sectional study included two groups of PwMS with 113 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…38 This discrepancy is perhaps because PwMS live with medical uncertainty from the time of diagnosis and thus have experience in dealing with the related discomfort. 32,39 The study results did not find that the type of medications used impacted PwMS' mental health. Past research regarding the behavioral practice of PwMS found that most did not stop taking their medications, though 46% reported experiencing fear and anxiety from taking disease-modifying therapy.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…38 This discrepancy is perhaps because PwMS live with medical uncertainty from the time of diagnosis and thus have experience in dealing with the related discomfort. 32,39 The study results did not find that the type of medications used impacted PwMS' mental health. Past research regarding the behavioral practice of PwMS found that most did not stop taking their medications, though 46% reported experiencing fear and anxiety from taking disease-modifying therapy.…”
Section: Methodsmentioning
confidence: 66%
“… 38 This discrepancy is perhaps because PwMS live with medical uncertainty from the time of diagnosis and thus have experience in dealing with the related discomfort. 32 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the specificity of the study group, the course of MS is highly unpredictable and is usually characterized by relapses and periods of symptom remission. Uncertainty about treatment outcomes and the high rate of disability progression, as well as the side effects of the therapies used, make it difficult for patients to adjust psychologically to the disease state and have a significant impact on their daily functioning, mental health ( 76 , 77 ), quality of life ( 78 ) and ability to cope ( 79 ). The search for meaning in life dimension represents the motivational aspect of meaning in life, which requires commitment and increased activity ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Durante os anos de 2019 a 2022 a covid-19 se alastrou por todo o mundo, sendo considerada pela Organização Mundial de Saúde uma pandemia em março de 2020 (WILSKI M, et al, 2022). O isolamento social foi a medida mais segura instaurada em todos os países até o desenvolvimento das vacinas e efeito populacional esperado.…”
Section: Introductionunclassified